IRF1 amplifies HSV-1-triggered antiviral innate immunity in a feed-forward manner - Ming Gao; Yining Qi; Junjie Zhang (Cell Insight)
Herpes simplex virus 1 (HSV-1) is a prevalent human pathogen that establishes lifelong infection and causes a wide range of diseases. Antiviral innate immunity is critical for controlling HSV-1 replication; however, how host cells elicit a full spectrum of antiviral innate immune responses against HSV-1 remains poorly understood. Here, our studies indicate that Interferon regulatory factor 1 (IRF1) amplifies HSV-1-induced antiviral innate immunity in a feed-forward manner. Our data reveal that HSV-1 infection induces IRF1 expression, and MITA/STING contributes to the induction of IRF1 during HSV-1 infection. Moreover, IRF1 restricts HSV-1 replication dependent on its DNA-binding activity. Knockout of IRF1 significantly diminishes the induction of a large subset of interferon-stimulated genes (ISGs) critical for antiviral defense during HSV-1 infection. Notably, IRF1 interacts with IRF3, promoting its recruitment to the promoters of ISGs as well as type I and III interferons, thereby facilitating the activation of antiviral signaling. These findings uncover a novel amplifying role of IRF1 in HSV-1-induced antiviral immunity, which deepens our understanding of innate immune responses against viral infections.